1979
DOI: 10.1152/jappl.1979.46.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in skeletal muscle following strength training

Abstract: Five men were studied before and after 7 wk of isokinetic strength training to determine its effects on muscle enzyme activities and fiber composition. One of the subject's legs was trained using 10 repeated 6-s maximal work bouts, while the other leg performed repeated 30-s maximal knee extension exercise. The total work accomplished by each leg was constant. Training 4 times/wk achieved similar gains in peak torque for both legs at the training velocity (3.14 rad/s) and at slower speeds. Fatigability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
1
13

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(106 citation statements)
references
References 12 publications
11
81
1
13
Order By: Relevance
“…The 5-6% increase in knee extensor cross-sectional area in consistent with other reports of change following 5 or 6 weeks of heavy resistance training (14, 24). Coyle et al (7) and Costill et al (6) have reported significantly increased cross-sectional area of type II fibers only following 6 and 7 weeks of training the knee extensors at 5.24 and 3.1 4 rad/sec, respectively. In contrast, MacDougall et al (15) have reported increased cross-sectional area of both type I and type II fibers following heavy resistance (slow velocity) training.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The 5-6% increase in knee extensor cross-sectional area in consistent with other reports of change following 5 or 6 weeks of heavy resistance training (14, 24). Coyle et al (7) and Costill et al (6) have reported significantly increased cross-sectional area of type II fibers only following 6 and 7 weeks of training the knee extensors at 5.24 and 3.1 4 rad/sec, respectively. In contrast, MacDougall et al (15) have reported increased cross-sectional area of both type I and type II fibers following heavy resistance (slow velocity) training.…”
Section: Discussionmentioning
confidence: 97%
“…More specifically, increased areas of type II muscle fibers have been reported (6,7) following training of the knee extensors at 3.14 and 5.24 radlsec. However, these results are not confidently offered as explanation for the enhanced performance and there is evidence to suggest that much of the training effect may be mediated by neurological adaptation (5,7,11,21).…”
mentioning
confidence: 98%
“…O ATP-CP é predominante em atividades musculares intensas e em ações de curta duração 22 . Além disso, a literatura apóia a ideía de melhoras no CMJ em relação ao 1RM 23 , sentar e levantar e foot up and go após seis semanas de treinamento de força e revelam que a melhora do desempenho das variáveis analisadas pode estar relacionada a fatores neurais (padrão de recrutamento, taxa de disparo e sincronização das unidades motoras) 2 e morfológicos (aumento da área de secção transversa e espessura muscular). De fato, nas semanas iniciais de treinamento de força, a ativação neural é predominante em relação aos fatores morfológicos [24][25][26][27] .…”
Section: Discussionunclassified
“…Genellikle lif türlerinin genetik olarak kararlı olduğu kabul edilir [32,33]. Ortalama bir popülasyonda kas liflerinin yaklaĢık %50-55'i tür I, yaklaĢık %30-35'i tür IIA ve yaklaĢık %15'i tür IIB'den oluĢur fakat bu yüzdeler bireysel farklılıklara göre değiĢir.…”
Section: Kas Lifi Farklılaşmasıunclassified